Cleavage of macromolecule (protein/polysaccharide)-phenolic bond in soybean cell wall through Lactobacillus casei and Lactobacillus helviticus mixed culture solid-state fermentation for chlorogenic acid extraction - Akpabli-Tsigbe, N.D.K.; Osabutey, J.; Mintah, B.K.; Tano-Debrah, K.; Ma, Y. (Food Bioscience, 2023)
Out of the available dietary sources use for chlorogenic acid extraction, soybean is new and cheap that could offer cost-effective chlorogenic acid production under solid-state fermentation (SSF). Consequently, the study aimed at investigating the cleavage of protein/carbohydrate-phenolic bond in heilong48 soybean (HS) variety via solid-state fermentation by Lactobacillus casei and Lactobacillus helviticus mixed culture for chlorogenic acid extraction with high yield and increased biological activity. A simplistic two-pot bioproduct optimization approach was used; first, screening (Plackett-Burman design) of SSF conditions and second, optimizing (Box Behnken design) the significant SSF conditions obtained from the former design. The liquid-solid (liquid:solid) ratio of 32:68 (0.47), incubation time of 48 h, pH of 5, and temperature of 50 ◦C were the best-optimized SSF conditions obtained from the chronological combinatory screening and optimization methods. These conditions gave a satisfactory SSF model, and correspondingly acceptable chlorogenic acid yield (9.20 ± 0.17 mg/g), fermentation efficiency (37.26 ± 0.73%), and 2,2-diphenyl-1-picrylhydrazyl free radical-scavenging activity (DPPH) (65.21 ± 2.05 μmol AA eq/g dry sample) results. The L. casei and L. helviticus mixed culture fermented heilong48 soybean (MCFHS) sample (under optimized SSF conditions) had high (p < 0.05) chlorogenic acid yield and 2,2-diphenyl-1-picrylhydrazyl free radical-scavenging activity than the raw heilong48 soybean flour (RHSF) sample. The effectiveness of the optimized solid-state fermentation conditions on the structural modifications of heilong48 soybean sample was confirmed by scanning electron microscopy, atomic force microscopy, and Fourier transform infrared results.
Research Article
Keywords: Chlorogenic acid; Solid-state fermentation; Lactobacillus casei; Lactobacillus helviticus